2011
DOI: 10.1093/brain/awr133
|View full text |Cite|
|
Sign up to set email alerts
|

Telomere shortening reduces Alzheimer’s disease amyloid pathology in mice

Abstract: Alzheimer's disease is a neurodegenerative disorder of the elderly and advancing age is the major risk factor for Alzheimer's disease development. Telomere shortening represents one of the molecular causes of ageing that limits the proliferative capacity of cells, including neural stem cells. Studies on telomere lengths in patients with Alzheimer's disease have revealed contrary results and the functional role of telomere shortening on brain ageing and Alzheimer's disease is not known. Here, we have investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
82
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 77 publications
9
82
2
1
Order By: Relevance
“…A study investigating the role of telomere shortening on plaque pathology using APP23 mice (a mouse model for Alzheimer's disease) crossed with telomerase knockout mice (mTerc −/− ) indicated that telomere shortening improved the spatial learning ability and decreased plaque load (Rolyan et al ., 2011). The study showed a change in morphology of G3 mTerc −/− microglia but did not display differences in expression of microglia proteins such as MHC II that are altered during activation.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating the role of telomere shortening on plaque pathology using APP23 mice (a mouse model for Alzheimer's disease) crossed with telomerase knockout mice (mTerc −/− ) indicated that telomere shortening improved the spatial learning ability and decreased plaque load (Rolyan et al ., 2011). The study showed a change in morphology of G3 mTerc −/− microglia but did not display differences in expression of microglia proteins such as MHC II that are altered during activation.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's is a neurodegenerative disease associated with aging (Rolyan et al, 2011). Currently, more than 35 million people around the world are effected, and this number is predicted to dramaticaly increase as life expectency is prolonged.…”
Section: Telomere and Alzheimer's Diseasementioning
confidence: 99%
“…(156,165) Although not immediately, telomere shortening in leukocytes and microglia can affect neuronal health by compromising the normal functions of these immune cells within the brain. (168,169) The roles of the immune system in the initiation and progression of Newcastle disease (ND) are being actively investigated. (170) Telomere shortening in immune cells, astrocytes and neurons could amplify oxidative stress-dependent senescence and secretion of proinflammatory mediators (senescence-associated secretory phenotype), results in diseases progression.…”
Section: Telomeres and Diseasesmentioning
confidence: 99%